What Influences Where They Give Birth? Determinants of Place of Delivery among Women in Rural Ghana - Kwamena Sekyi Dickson; Kenneth Setorwu Adde; Hubert Amu (Hindawi Limited, 2016)
Background. There is a paucity of empirical literature in Ghana on rural areas and their utilisation of health facilities. The study examined the effects of the sociodemographics of rural women on place of delivery in the country. Methods. The paper made use of data from the 2014 Ghana Demographic and Health Survey. Women from rural areas who had given birth within five years prior to the survey were included in the analysis. Descriptive analyses and binary logistic regression were used to analyse the data. Results. Wealth, maternal education, ecological zone, getting money for treatment, ethnicity, partner's education, parity, and distance to a health facility were found as the determinants of place of delivery among women in rural Ghana. Women in the richest wealth quintile were three times (OR = 3.04, 95% CI = 0.35-26.4) more likely to deliver at a health facility than the poorest women. Conclusions. It behoves the relevant stakeholders including the Ghana Health Service and the Ministry of Health to pay attention to the wealth status, maternal education, ecological zone, ethnicity, partner's education, parity, and distance in their planning regarding delivery care in rural Ghana.